(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The new pandemic COVID-19 has sent shockwaves across the world but it has given birth to a new era of thinking and implementation. Nature redesigned the world’s beauty with its self healing feature. Before this pandemic, Remote learning was always considered a poor substitute experience for learning, but the COVID-19 situation has changed the teaching and learning methods across the globe. The spread of the COVID-19 pandemic all over the world adversely affects Global hyperconnectivity disturbing Global business. this pandemic has enhanced the essentiality of smarter tools for the prevention and protection of human beings. The world needs stronger, unified responses to our highest-priority health threats. It is the need for the new era to develop stronger solutions as the highest priority to fight against such new pandemics and sustain the present as well as future generations.